GLOBAL AND DISAGGREGATED MEASURES OF EARNINGS MOBILITY: EVIDENCE FROM FIVE EUROPEAN COUNTRIES. (16th June 2016) - Vittori, Claudia; Gregg, Paul
ABSTRACT: This paper offers the first application of the local approximation method pioneered by Schluter and Trede (2003) for the Shorrocks mobility indices across the earnings distribution for a range of European Countries covering the main European social models: Denmark, Germany, Spain, the UK and Italy in the pre‐accession EU (1994‐2001). This insightful approach allows us to offer a global and disaggregate analysis of mobility as proportionate change in inequality and hence provide the reader with a full set of information to make his/her own judgment about the extent of mobility and country ranking. Specifically, we investigate the degree to which mobility is driven by low or high earners and how this picture changes across three different earnings measures: full‐time full‐year working, adding part‐time working and then part‐year working. Our results draw out some general key facts. First of all the vast bulk of the measured mobility occurs in the tails especially the lower tail with at least half of the index driven by mobility in the bottom earning quintile. Second, in the top 20 percent of the distribution there are few movements of earnings that effect the level of permanent inequality except in Denmark. Third, no country has a clear dominance for mobility across the full earnings distribution but Denmark differs from the other countries with clearly greater mobility in the middle and at the top. Finally, we find that with the exception of Denmark and Italy, mobility does not lead to clear convergence to the mean but rather to points around 0.7‐0.8 and 1.5 to 2 times the mean.